Inhibitory control and problem solving in early childhood: Exploring the burdens and benefits of self-control - Hendry, A; Agyapong, MA; D'Souza, H; Et al. (Wiley, 2022)
Low inhibitory control (IC) is sometimes associated with enhanced problem-solving amongst adults, yet for young children high IC is primarily framed as inherently better than low IC. Here, we explore associations between IC and performance on a novel problem-solving task, amongst 102 English 2- and 3-year-olds (Study 1) and 84 Swedish children, seen at 18- months and 4-years (Study 2). Generativity during problem-solving was negatively associated with IC, as measured by prohibition-compliance (Study 1, both ages, Study 2 longitudinally from 18-months). High parent-reported IC was associated with poorer overall problem-solving success, and greater perseveration (Study 1, 3-year-olds only). Benefits of high parent-reported IC on persistence could be accounted for by developmental level. No concurrent association was observed between problem-solving performance and IC as measured with a Delay-of-Gratification task (Study 2, concurrent associations at 4-years). We suggest that, for young children, high IC may confer burden on insight- and analytic-aspects of problem-solving.